2015
DOI: 10.1557/mrs.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Materials challenges in three-dimensional integrated circuits

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Applying heat slowly removes vicinal (hydrogen-bonded) silanols by condensation and elimination of water (Equation 2) [25,26]. (1) The silanols can also react with to generate well-defined charge transfer species (as depicted by Equation 2). In fact reactions are essential for metal barrier films to bind to the isolation liner dielectric [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying heat slowly removes vicinal (hydrogen-bonded) silanols by condensation and elimination of water (Equation 2) [25,26]. (1) The silanols can also react with to generate well-defined charge transfer species (as depicted by Equation 2). In fact reactions are essential for metal barrier films to bind to the isolation liner dielectric [27].…”
Section: Resultsmentioning
confidence: 99%
“…This situation is further complicated by the introduction of new materials and integration schemes; for example, the commercial introduction of three dimensional integrated circuits (3D-ICs) has been hindered by reliability challenges, such as stress related failures, resistivity changes, and unexplained early failures [1,2]. The performance demands of such devices appear to conflict with the need for reliability.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Joule heating from the powered micro-bumps was transferred horizontally to the bottom of the neighboring un-powered micro-bumps, creating a large temperature gradient on the order of 1000 • C/cm through the un-powered micro-bumps in the neighboring chip, such that the latter failed due to thermomigration. Recently, due to the diameter of micro-bumps being lower than 20 µm, the whole micro-bump has mostly been constituted by IMC after reflow [83]. Previous work about the reliability of micro-bumps has focused on the mechanical properties of the IMC [84] and the comparison of the resistance to EM and TM (thermo-migration) of the IMC to Pb-free solder [85,86].…”
Section: Micro-bump Electromigration and Heat Transfermentioning
confidence: 99%
“…This situation is further complicated by the introduction of new materials and integration schemes; for example, the commercial introduction of three dimensional integrated circuits (3D-ICs) has been hindered by reliability challenges, such as stress related failures, resistivity changes, and unexplained early failures[1, 2]. The performance demands of such devices appear to conflict with the need for reliability.…”
Section: Introductionmentioning
confidence: 99%